The impact of multilingualism on achieving linguistic development: Algeria as a model - Fatima Zahra , Fatima Zahra; mendil, naouel (El Omda in Linguistics and Discourse Analysis, 2023)
Abstract : Multilingualism is commonto all Languages common to all languages The language connects the individual and the linguistic group it is means of communication and exchange of oponions and ideas without language man far from his society it does not contribute any interaction take the field of neutrality The cultural language of all peoples . Linguage helps achieve linguistics social and economic development in light of globalization under shadow globalization technology development and rapid number transformation .